Peran Internet of Things (IoT) dalam Mengoptimalkan Rantai Pasok E-commerce: Systematic Literature Review - Putri, Anggun Cynthia; Nasihin, Muhamad (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
This study identifies and analyzes the role of the Internet of Things (IoT) in optimizing the supply chain in the e-commerce sector through a Systematic Literature Review approach. By evaluating the literature from 2020 to 2024, this study shows that IoT can improve operational efficiency, transparency, and automation in supply chain management. Key findings reveal that IoT technology can reduce reliance on inefficient manual processes, allowing companies to monitor the condition of goods and logistics status in real-time. This contributes to faster decision-making and improved customer satisfaction. However, the research also found challenges in implementing IoT, such as the complexity of system integration, high initial investment requirements, and data security and privacy issues. Therefore, companies need to plan a well-thought-out strategy to overcome these obstacles. This research emphasizes the importance of collaboration between stakeholders to create an ecosystem that supports IoT adoption. Overall, this research provides valuable insights into the potential and challenges of IoT adoption, and recommends further research to ensure competitiveness in the digital age.